Peningkatan Kemandirian Belajar Matematika Melalui Strategi Discovery Learning Pada Siswa Kelas VII Semester Genap SMP Negeri 1 Sambi Tahun 2014/2015 - Setiyadi, Aji Gunawan, Prof. Dr. Sutama, M.Pd (2015)
The aim of research is to describe the increase in the independence of graders learn math VIIG SMP Negeri 1 Sambi after learning by discovery learning strategy. Qualitative research class action. Methods of data collection observation, field notes, interviews and documentation. Data analysis techniques with methods groove through three stages, data reduction, data presentation, and inference. Validity of data with triangulation of methods and sources. Results showed improvement of students' mathematics learning independence views of: 1) students who have a sense of responsibility from the initial conditions (32.35%), in the first cycle (50.00%) and the second cycle (70.59%), students which does not depend on others from the initial conditions (29.41%), in the first cycle (52.94%) and the second cycle (73.53%), 3) students have a great curiosity from the initial conditions (17 , 65%), in the first cycle (29.41%) and the second cycle (47.06%), 4) students who have the confidence of the initial conditions (8.82%), in the first cycle (20.59 %) and the second cycle (50.00%). It can be concluded that learning with application discovery learning strategies can improve mathematics learning independence. Keywords: mathematics learning, discovery learning, independent learning.